Emulsion‐templated synthesis of 3D evaporators for efficient solar steam generation. Issue 2 (9th August 2022) - Chen, Jinxing; Lee, Michael; Qiu, Yinghua; Wu, Chaolumen; Li, Bo; Yin, Yadong
Abstract: Interfacial solar steam generation holds great promise in water desalination thanks to its high energy efficiency by heating only the top layer of water for evaporation. While three‐dimensional (3D) evaporators have been proven to increase the evaporation rate by harnessing the energy from the surroundings, further development is still required in terms of convenient fabrication with potential scalability. Herein, we propose to overcome this challenge by using a high internal phase emulsion (HIPE) to template the synthesis of 3D hierarchically porous evaporators. The HIPE‐templated synthesis combined with a molding process can efficiently fabricate the desired 3D shape without wasting any materials and generate a hierarchically porous internal structure for continuous water supply. Engineering the overall shape and internal pores produces a 3D evaporator that can suppress conduction heat loss and efficiently collect thermal energy from its surroundings, boosting the evaporation rate to 2.82 kg/(m 2  h) under 1‐sun illumination, which is significantly higher than conventional 2D evaporators. HIPE‐templating synthesis is an easy but effective way to produce various porous polymers, promising for a wide range of applications where easy production, excellent shape control, and potential scalability are critical. Abstract : This study provides a high internal phase emulsion‐templating method for synthesizing three‐dimensional evaporators, which can suppress conduction heat loss and efficiently collect thermal energy from the surroundings, boosting the evaporation rate to 2.82 kg/m 2  h) under 1‐sun illumination.